1H, 15N, and 13C Resonance Assignments of the Anti-CRISPR AcrIIA4 from Listeria monocytogenes Prophages - 김익태; 김낙균; 서정용 (한국자기공명학회, 2018)
The CRISPR-Cas system is the adaptive immune system in bacteria and archaea against invading phages or foreign plasmids. In the type II CRISPR-Cas system, an endonuclease Cas9 cleaves DNA targets of phages as directed by guide RNA comprising crRNA and tracrRNA. To avoid targeting and destruction by Cas9, phages employ anti-CRISPR (Acr) proteins that act against host bacterial immunity by inactivating the CRISPR-Cas system. Here we report the backbone 1H, 15N, and 13C resonance assignments of AcrIIA4 that inhibits endonuclease activity of type II-A Listeria monocytogenes Cas9 and also Streptococcus pyogenesis Cas9 using triple resonance nuclear magnetic resonance spectroscopy. The secondary structures of AcrIIA4 predicted by the backbone chemical shifts show an alpha-beta-beta-beta-alpha-alpha fold, which is used to determine the solution structure.